Epidemiological Study of Common Cancer Cases in Baghdad City - Taghreed Khudhur Mohammed1 , Alaaabdulkhaliq Jabbar2 , Anam Aziz Jasim3 , Hanaa N. Abdullah4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: It is possible to notice the increase in the incidence of cancer during the recent years in Iraq, particularly in Basrah, Al - Anbar and Baghdad. Different types of cancers like l Lung cancer, Breast cancer, Bladder cancer, Colorectal cancer and Pancreas tumors. Objectives: The objective of the current research was to study the most common cancer cases in Baghdad city. Method: The current study was conducted in the oncology teaching hospital/medical city/Baghdad, for the period from January 2019 until October 2019. The data of 139 patients were collected from official records in the hospital clinics which included gender, age and the types of cancer. Results: The highest percentage of cancers was found in patients with breast cancer (54.67 %); followed by colon cancer (16.54 %), ovarian cancer (8.63 %), liver cancer (5.75 %) and prostate cancer (5.03 %). The highest incidence of breast cancer appeared in the age group (40 – 49) years with the percentage of 35.52%. Of the total number of studied cases, 80 (63.30%) of patients with different types of cancer suffered from chronic diseases. Conclusion: Breast cancer mostcommon types of cancers in Baghdad city, and inceased cases in the last year, 2019. Both sexes suffered from cancers especially in age above 40 years.